PENGARUH VIDEO PROSES PERSALINAN NORMAL TERHADAP KECEMASAN IBU HAMIL MENGHADAPI PERSALINAN - Yuniarti, Yuniarti (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Anxienty facing labor primigravida’s. The aims of study was to determine the differences of primigravida’s anxiety in facing labor after given counseling by watching normal labor process video in Independent Practice Midwife Bengkulu City in 2013. This research method was a type of analytical study design with Quasi experiments with pre-test and post-test approach. The sample consisted of group counseling and group watched a video that was 60 with a ratio of 1:1 corresponding inclusion and exclusion criteria. Data were analyzed using univariate, bivariate and multivariate. The results showed no difference in anxiety in the face of labor primigravida after counseled by watching videos of normal deliveries (p= 0.000). Multivariate results show that education affects the level of anxiety after watching the video and counseling on the normal birth process primigravida (p= 0.009).